Soldiers and Societies in Postcommunist Europe
IX, 264 p. 7 illus.
Keywords: This major comparative study examines the development of military-society relations in central and eastern Europe since the collapse of communism. Soldiers and Societies in Post-Communist Europe explores how the interaction of the common challenges of postcommunism and the diverse circumstances of individual countries are shaping patterns of military-society relations in this changing region. Detailed country case studies, written by international experts to a common analytical framework, compare the experiences of Poland, the Czech Republic, Slovakia, Hungary, Latvia, Lithuania, Romania, Bulgaria, Slovenia, Croatia, Yugoslavia and Ukraine.